2021
DOI: 10.3389/fgene.2021.762678
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Long Non-Coding RNAs and Their Potential Functions in Poplar Growth and Phenylalanine Biosynthesis

Abstract: Poplar is an important bioenergy tree species. lncRNAs play important roles in various biological regulatory processes, and their expression pattern is more tissue-specific than mRNAs. In this study, P. deltoides “Danhong” (Pd) and P. simonii “Tongliao1” (Ps) with different growth rates and wood quality were used as experimental materials, and the transcriptomes of their shoot apical meristem, xylem, and phloem were sequenced. Furthermore, high-throughput RNA sequencing analysis revealed that the expression pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…[ 85 ]—identifies the role of miRNAs in phenylpropanoids, terpenoids, and alkaloids biosynthesis in medicinal plants; ref. [ 86 ]—is focused on lncRNAs regulatory potential in Populus trichocarpa Torr. & Gray phenylpropanoid pathway; ref.…”
Section: The Involvement Of Mirna In Plant Lignan Biosynthesismentioning
confidence: 99%
“…[ 85 ]—identifies the role of miRNAs in phenylpropanoids, terpenoids, and alkaloids biosynthesis in medicinal plants; ref. [ 86 ]—is focused on lncRNAs regulatory potential in Populus trichocarpa Torr. & Gray phenylpropanoid pathway; ref.…”
Section: The Involvement Of Mirna In Plant Lignan Biosynthesismentioning
confidence: 99%
“…In addition to coding RNA, non-coding RNA also plays an important role in plant transcriptional regulation ( Liu et al, 2015 ; Liaquat et al, 2021 ; Zhang et al, 2021 ). Previous study has shown that transcriptome sequencing on the mature xylem tissues of NW, TW, and OW reveals 1,377 possible lncRNAs, of which 776 are differentially expressed in different tissue samples of poplar ( Chen et al, 2015b ).…”
Section: Discussionmentioning
confidence: 99%
“…Wood formation is a continuous and highly ordered biological process involved in vascular cambium differentiation, vascular tissue division, cell expansion, cell wall thickening, and programmed cell death (S. Li, Zhang et al., 2020), and is controlled by multi‐level regulations, such as transcriptional regulation (Jiang et al., 2022; Y. Liu et al., 2017; Nakano et al., 2015; Ren et al., 2022; Ye & Zhong, 2015), post‐translational regulation (Kawabe et al., 2018; Morse et al., 2009; Sulis & Wang, 2020; Zhong & Ye, 2009), and epigenetic regulation (Mizrachi & Myburg, 2016; L. Zhang, Ge, et al., 2021), which are organized in a sophisticated network that coordinately integrate developmental and environmental cues into wood formation (Taylor‐Teeples et al., 2015). Among these epigenetic regulation model, the miRNA and methylation regulations have been reported to widely participate in wood formation (R. Wang et al., 2021; Y. Zhang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%